Microbiome analysis and predicted relative metabolomic turnover suggest bacterial heme and selenium metabolism are altered in the gastrointestinal system of zebrafish (Danio rerio) exposed to the organochlorine dieldrin - Hua, Qing; Adamovsky, Ondrej; Vespalcova, Hana; Boyda, Jonna; Schmidt, Jordan T; Kozuch, Marianne; Craft, Serena L M; Ginn, Pamela E; Smatana, Stanislav; Budinska, Eva; Persico, Maria; Bisesi, Joseph H; et al. (Environmental pollution (Barking, Essex, 2021)
Dietary exposure to chemicals alters the diversity of microbiome communities and can lead to pathophysiological changes in the gastrointestinal system. The organochlorine pesticide dieldrin is a persistent environmental contaminant that bioaccumulates in fatty tissue of aquatic organisms. The objectives of this study were to determine whether environmentally-relevant doses of dieldrin altered gastrointestinal morphology and the microbiome of zebrafish. Adult zebrafish at ∼4 months of age were fed a measured amount of feed containing either a solvent control or one of two doses of dieldrin (measured at 16, and 163.5 ng/g dry weight) for 4 months. Dieldrin body burden levels in zebrafish after four-month exposure were 0 (control), 11.47 ± 1.13 ng/g (low dose) and 18.32 ± 1.32 ng/g (high dose) wet weight [mean ± std]. Extensive histopathology at the whole organism level revealed that dieldrin exposure did not induce notable tissue pathology, including the gastrointestinal tract. A repeated measure mixed model analysis revealed that, while fish gained weight over time, there were no dieldrin-specific effects on body weight. Fecal content was collected from the gastrointestinal tract of males and 16S rRNA gene sequencing conducted. Dieldrin at a measured feed dose of 16 ng/g reduced the abundance of Firmicutes, a phylum involved in energy resorption. At the level of class, there was a decrease in abundance of Clostridia and Betaproteobacteria, and an increase in Verrucomicrobiae species. We used a computational approach called predicted relative metabolomic turnover (PRMT) to predict how a shift in microbial community composition affects exchange of metabolites. Dieldrin was predicted to affect metabolic turnover of uroporphyrinogen I and coproporphyrinogen I [enzyme]-cysteine, hydrogen selenide, selenite, and methyl-selenic acid in the fish gastrointestinal system. These pathways are related to bacterial heme biosynthesis and selenium metabolism. Our study demonstrates that dietary exposures to dieldrin can alter microbiota composition over 4 months, however the long-term consequences of such impacts are not well understood.
Keywords: Microbiome; selen; hem; mikrobiota; Aquatic; dánio pruhované; RNA ribozomální 16S; Microbiota; zvířata; RNA, Ribosomal, 16S; Selenium; Dieldrin; Zebrafish; Male; dieldrin; Ecotoxicology; Pathology; Animals; mužské pohlaví; Heme; Gastrointestinal Tract; gastrointestinální trakt; Pesticide